2013
DOI: 10.1021/jm4017202
|View full text |Cite
|
Sign up to set email alerts
|

A “Ship in a Bottle” Strategy To Load a Hydrophilic Anticancer Drug in Porous Metal Organic Framework Nanoparticles: Efficient Encapsulation, Matrix Stabilization, and Photodelivery

Abstract: An essential challenge in the development of nanosized metal organic framework (nanoMOF) materials in biomedicine is to develop a strategy to stabilize their supramolecular structure in biological media while being able to control drug encapsulation and release. We have developed a method to efficiently encapsulate topotecan (TPT, 1), an important cytotoxic drug, in biodegradable nanoMOFs. Once inside the pores, 1 monomers aggregate in a "ship in a bottle" fashion, thus filling practically all of the nanoMOFs'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 48 publications
3
86
0
Order By: Relevance
“…161 Cytotoxicity assays in HepG2 and MCF-7 cells showed that AL-UiO-66 NMOFs induced enhanced cell killing than free AL. The delivery of camptothecin (CPT) and its derivative Topotecan (TPT) was achieved by ZIF-8 (∼70 nm) 162 and MIL-100 (∼50−100 nm), 163 respectively. Both drug loaded NMOFs exhibited enhanced cytotoxicity against cancer cells as compared to free drugs.…”
Section: Doxorubicin (Dox)mentioning
confidence: 99%
“…161 Cytotoxicity assays in HepG2 and MCF-7 cells showed that AL-UiO-66 NMOFs induced enhanced cell killing than free AL. The delivery of camptothecin (CPT) and its derivative Topotecan (TPT) was achieved by ZIF-8 (∼70 nm) 162 and MIL-100 (∼50−100 nm), 163 respectively. Both drug loaded NMOFs exhibited enhanced cytotoxicity against cancer cells as compared to free drugs.…”
Section: Doxorubicin (Dox)mentioning
confidence: 99%
“…[11][12][13] Others have been designed to emit white light for developing white light emitting devices (WLEDs). 18,19 The formed host-guests composites materials can exhibit different photoevents processes as charge-and energy-transfer (CT, ET). 16,17 For both MOFs, the immobilization of the organic linkers by its incorporation into the network leads to an increase in the internal as well as external quantum yields, improving their photoluminescence properties, like luminescent and moisture stability and color tunability.…”
Section: Introductionmentioning
confidence: 99%
“…16 Other than these, the microenvironment of MOFs which are either hydrophilic or hydrophobic gives them ability to encapsulate both lipophilic as well as lipophobic drugs. 17 Different types of forces play an important role for drug loading and its release. These forces can be Van Der Waals force, hydrogen bonds, coordination bond, pi-pi interactions, electrostatic interaction etc.…”
mentioning
confidence: 99%